Respostas
respondido por:
2
Resolução:
= (x-20)^3
= (x-20)^2 . (x-20)
= (x^2 - 2.20.x + 20^2).(x-20)
= (x^2 - 40x + 40).(x-20)
= x^3 - 20x^2 - 40x^2 + 80x + 40x - 800
R.:
= x^3 - 60x^2+ 120x - 800
respondido por:
2
Resposta:
(x - 20)³ = x³ - 60x² + 1200x - 8000
Explicação passo-a-passo:
(x - 20)² = (x - 20)(x - 20)² = ( x - 20)(x² -2.x.20 + 20²) = (x - 20)(x² - 40x + 400)=
x³ - 40x² + 400x - 20x² + 800x - 8000 = x³ - 60x² + 1200x - 8000
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás